2021
DOI: 10.1101/2021.03.30.437691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multimodal genomic markers predict immunotherapy response in the head and neck squamous cell carcinoma

Abstract: Immune checkpoint blockade (ICB) therapy has had a major impact on the clinical management of head and neck squamous cell carcinoma (HNSCC). However, clinical responses to ICB are observed in only a fraction of patients. In the present paper, we used multimodal approaches to a) evaluate the utility of existing ICB biomarkers including tumor mutation burden (TMB), microsatellite instability (MSI), and a T-cell specific signature in predicting therapy response in HNSCC using TCGA cohort, and; b) identify a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
2
3
1
Order By: Relevance
“…In concordance with two other reports on patients with HNSCC [34,44], this study found that TMB was associated with tumor location in a statistically significant way. The proportion of patients with laryngeal tumors was significantly increased, and oropharyngeal cancer decreased, in the TMB-(6+) group when compared to patients with any other throat tumor location.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In concordance with two other reports on patients with HNSCC [34,44], this study found that TMB was associated with tumor location in a statistically significant way. The proportion of patients with laryngeal tumors was significantly increased, and oropharyngeal cancer decreased, in the TMB-(6+) group when compared to patients with any other throat tumor location.…”
Section: Discussionsupporting
confidence: 93%
“…Although the split of TMB between groups was based on Foundation Medicine guideline, the groups would be similar for a threshold based on median TMB, with 70 patients in the TMB-(<6) group and 58 patients in the TMB-(6+) group. Similar to the reports in HN-SCC [27,28] and in other malignancies [24,33,34], this study demonstrated that there was no significant relationship between PD-L1 and TMB, reflecting the dynamic interactions between the two variables.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations